Critical Synthesis Package: Chronic Fatigue Syndrome Attitudes Test (CAT) - Jennifer Coleman; Jennifer Joy-Gaba (Association of American Medical Colleges, 2015)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and the application to health science education of the Chronic Fatigue Syndrome Attitudes Test (CAT), and (2) a copy of the CAT and scoring key developed by Leonard Jason, PhD. The CAT is a 13-item self-report scale that assesses individuals' attitudes toward people with chronic fatigue syndrome (CFS). The items form three factors of: Responsibility for CFS, Relevance of CFS, and Traits of People with CFS. The CAT can be used with a variety of populations and across diverse contexts. The scale uses a 7-point Likert-type scale (1 = strongly disagree, 7 = strongly agree). Of these items, one is negatively worded and requires reverse scoring. The composite score ranges from 13 to 91, with higher scores indicating more negative attitudes towards individuals with CFS. Upon examination, only one study provided validity evidence for the CAT. The current analysis revealed that the CAT has various strengths including: both positively and negatively worded items, 6-week test-retest reliability, internal consistency reliability for subscales ranging from .63 to .75, and validity as evidenced by significant correlations with other scales assessing attitudes toward stigmatized groups. Moreover, the authors conducted a factor analyses to finalize items. Future researchers may wish to use the CAT to determine whether medical providers' attitudes towards individuals with CFS impact quality of treatment or interactions. The CAT may also be used in research to explore whether attitudes towards individuals with CFS differ based on demographic characteristics. Finally, although initial evidence of reliability and validity has been found satisfactory, future researchers are encouraged to further assess psychometric properties of the measure.